(untitled) (Bangladesh Journal of Microbiology, 2008)
Keratinolytic protease is an inducible specific proteolytic enzyme, which is produced by Bacillus licheniformis MZK-03 in presence of keratin (feather mill) as sole carbon and nitrogen source in growth medium. Maximum level of keratinolytic protease was produced after 42 h at 37°C over a wide range of initial pH (5.0 to 12.0) under continuous agitation (200 rpm). Keratinolytic protease worked best at 37°C and at pH 8.5. The enzyme was quite stable over a wide range of pH (7.0 to 11.0) but activity dropped drastically beyond this level (enzyme activity dropped to 8.8% and 19.3% at pH 6.5 and 12.0, respectively). Half-life of keratinolytic protease at 70° and 60°C were found to be 3 and 7 min respectively. The enzyme showed highest stability at 40°C (>90% after 3 h). The half-life at 4°C was 34 days. The presence of metal ions (5 mM) like Mg2+, Mn2+, Ca2+ and K+ had no remarkable effect on the keratinolytic protease activity but the activity decreased in presence of Hg2+ and Cu2+. The enzyme may belong to serine protease group as it is inhibited by serine protease inhibitor phenyl methyl sulphonyl fluoride (PMSF). The enzyme is as compatible as other commercially available enzymes used in leather industry with tannery chemicals. It was completely incompatible with Na2S and CaO for their high alkalinity (pH >13.0), which was also observed for other commercial enzymes except the commercial enzyme supplemented with ammonium sulphate. Keywords: Bacillus licheniformis MZK-03, Keratinolytic protease, Keratin, Production, Characterization DOI: http://dx.doi.org/10.3329/bjm.v24i1.1239 Bangladesh J Microbiol, Volume 24, Number 1, June 2007, pp 57-61